The conventionalisation of contextual effects in middle structures - Garcia de la Maza, Casilda (International Journal of English Studies, 2013)
The presence of adverbial modification, affectedness, or the aspectual characteristics of the verb phrase have usually been invoked as principles governing the possibility for a verb to appear in the middle mode, as defended by Roberts (1987), Fagan (1992), Doron and Rappaport-Hovav (1991) and Levin (1993), inter al. This paper presents the results of a data collection project aimed at unravelling the issue of the conditions on middle formation. The data show how existing accounts are deficient in a number of ways and leave a wide range of data unaccounted for. Instead, the data reveal that pragmatic relevance has a major role to play in the matter and provide empirical support to defend the essentially “pragmatic value” (Green 2004) of the construction. Some of the formal properties of middles which had been formerly put down to syntactic constraints are then reanalysed in the light of this characterisation, including the apparent requirement for adverbial modification, which can now be approached from a fresh perspective.